OPTIMIZING BUSINESS STRATEGIES THROUGH THE APPLICATION OF PRODUCT–SERVICE SYSTEMS (PSS) AT TUANG RUANG - Chelsea Regita Gloria Hutagalung; Nanang Alamsyah; Mohammad Rachman Waluyo; Wendy Febrianty Mardhiyah (Journal of Business Studies and Management Review, 2025)
This study analyzes the optimization of business strategies through the application of Product–Service Systems (PSS) at Tuang Ruang, a construction-based enterprise that integrates architectural design and creative services. Although the company has adopted basic PSS elements, its current implementation remains limited and requires strategic enhancement to strengthen competitiveness and long-term sustainability. Using a qualitative descriptive approach supported by interviews, field observations, and PSS quadrant assessment, this research evaluates Tuang Ruang’s product–service integration and identifies opportunities for advancing its business model. The results indicate that the company currently aligns with Quadrant 3, which emphasizes advisory and consulting services. However, further analysis reveals several eligible quadrants that offer greater strategic potential, including Product Related Service (Quadrant 2), Advice & Consulting (Quadrant 3), Outsourcing (Quadrant 8), Pay Per Service Unit (Quadrant 9), and Functional Result (Quadrant 10). Proposed strategic directions include developing a digital application equipped with self-design and project monitoring features, establishing a dedicated architectural consultation studio, forming partnerships with third-party software providers, implementing flexible pay-per-use service schemes, and adopting performance-based contracting models. These initiatives support the transition toward a more integrated service-oriented framework that enhances operational efficiency, customer experience, and market competitiveness. Overall, the PSS-based strategy offers significant potential to transform Tuang Ruang into a more adaptive, innovative, and sustainable construction service provider.